2020
DOI: 10.1590/1806-3713/e20190003
|View full text |Cite
|
Sign up to set email alerts
|

Robotic thoracic surgery for non-small cell lung cancer: initial experience in Brazil

Abstract: Objective: To describe the morbidity, mortality, and rate of complete resection associated with robotic surgery for the treatment of non-small cell lung cancer in Brazil, as well as to report the rates of overall survival and disease-free survival in patients so treated. Methods: This was a retrospective study of patients diagnosed with non-small cell lung carcinoma and undergoing resection by robotic surgery at one of six hospitals in Brazil between February of 2015 and July of 2018. Data were collected retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 18 publications
1
5
0
12
Order By: Relevance
“…Although the studies detailed above describe initial experiences in Brazil, (4,5) the morbidity and mortality rates reported are very similar to those reported in various international studies, (6) demonstrating that robotic surgery results in pleural drainage times and hospital stays are shorter than those reported for other techniques. (7) Oh et al (8) published results from a study of patients who underwent lobectomy in the USA.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…Although the studies detailed above describe initial experiences in Brazil, (4,5) the morbidity and mortality rates reported are very similar to those reported in various international studies, (6) demonstrating that robotic surgery results in pleural drainage times and hospital stays are shorter than those reported for other techniques. (7) Oh et al (8) published results from a study of patients who underwent lobectomy in the USA.…”
supporting
confidence: 71%
“…This issue of the JBP includes the largest studies to date presenting the Brazilian experience with robotic surgery in the treatment of tumors of the thymus (4) and lung cancer. (5) Terra et al (4) report their initial experience in a sample of 18 patients with tumors of the thymus who underwent robotic surgery at a total of seven centers in Brazil. The authors reported technical aspects and results, such as operative time, extent of resection, length of hospital stay, and postoperative complications.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(29) Outro fator que pode ter contribuído para a queda da mortalidade no período mais recente foi a melhora da técnica cirúrgica através do aumento na proporção de cirurgias minimamente invasivas, principalmente por videotoracoscopia, mas também pela via robótica, essa última iniciada em 2015. (30,31) A cirurgia mais realizada foi a lobectomia, correspondendo a mais de 80% dos casos nos dois períodos. Entretanto, observamos um aumento significativo da realização de segmentectomias no período mais recente, conforme tendência da literatura cirúrgica atual que reforça os benefícios de ressecções sublobares, surgindo como opção à lobectomia em pacientes com função pulmonar limitante, doença multifocal (32) ou doença inicial.…”
Section: Discussionunclassified